Enhanced Photocatalytic Activity of Hydrothermally Synthesized Perovskite Strontium Titanate Nanocubes - Kiran, K. S.; Shashanka, R.; Lokesh, S., V (Springer/Plenum Publishers, 2025)
Strontium titanate (SrTiO3) nanoparticles are one of the ideal and inexpensive perovskites used extensively as photocatalysts. In the present paper, Strontium titanate nanocubes (STNCs) were successfully fabricated by a hydrothermal technique using titanium dioxide and strontium nitrate (Sr(NO3)(2)) as precursors. The X-ray diffraction studies revealed the crystallinity of the fabricated STNCs and the diffraction pattern was well-matched with standard SrTiO3 data. The scanning electron microscope, and transmission electron microscope confirmed the perovskite structure with a regular cubic phase and a refined particle sizes of similar to 18 nm. The energy dispersive spectrometer study showed that the mole ratio of Sr and Ti (Sr/Ti) are well-matched with the precursors used initially for the synthesis of STNCs. The synthesized STNCs showed excellent photocatalytic degradation of Methylene Blue (MB) and Tartrazine (TZ) dye under UV light irradiation with the kinetic study. Around 78.9 and 76.4% of degradation of MB and TZ dye was achieved successfully under UV light using fabricated STNCs with the respective rate of 3.713 x 10(-3) and 3.56 x 10(-3) min(-1). The reusability test for prepared STNCs was also conducted to estimate the efficiency of the catalyst.
Keywords: Srtio3 Nanocubes; Hydrothermal Method; Perovskite; Methylene Blue; Tartrazine